OPEN SOURCE ERP IMPLEMENTATION AID TOOL FOR FASHION SMES - PRATAMA (NIM : 13414047), JAMES
Enterprise Resource Planning (ERP) is a software to help people manage various business activities in a company. The company can be both big scaled or small scaled company (SME). But, the usage of ERP on Indonesian SME is still low until now. It can be assumed that Indonesian SME is reluctant to use ERP on their company because they are concerned about the cost, risks, and complexity of ERP implementation. The purpose of this research is to overcome the problems by using open source ERP with an implementation aid tool. The implementation aid tool is designed for small scaled fashion company, which is growing rapidly in Indonesia these days. The aid tool design process begins with development of ERP implementation methodology for SME based on SAP methodology (ASAP methodology) and Microsoft Dynamics Sure Step methodology. Then, an implementation project at PT Cahaya Perada Abadi (a small scaled fashion company in Bandung) was held. The method used in the implementation project is literature study and interview with PT Cahaya Perada Abadi’s management. This method is considered compatible with the research because the data needed for this research is qualitative and this research mainly focused on understanding SME’s business process and requirements. Based on this research, the implementation methodology can be declared valid and capable of guiding an ERP implementation project on SME. Moreover, Odoo Community, the chosen ERP provider, can also be declared capable of fulfilling fashion SME’s requirements with the help of the ERP implementation aid tool.